2024
DOI: 10.3389/fimmu.2024.1360065
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols: immunonutrients tipping the balance of immunometabolism in chronic diseases

Carolina Ferreira,
Pedro Vieira,
Helena Sá
et al.

Abstract: Mounting evidence progressively appreciates the vital interplay between immunity and metabolism in a wide array of immunometabolic chronic disorders, both autoimmune and non-autoimmune mediated. The immune system regulates the functioning of cellular metabolism within organs like the brain, pancreas and/or adipose tissue by sensing and adapting to fluctuations in the microenvironment’s nutrients, thereby reshaping metabolic pathways that greatly impact a pro- or anti-inflammatory immunophenotype. While it is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 336 publications
(272 reference statements)
0
1
0
Order By: Relevance
“…This lack of identification means we cannot attribute the antioxidant properties to these compounds specifically. The increase in radical scavenging capacity, despite a decrease in known antioxidant compounds like polyphenols, suggests that other non-polyphenolic compounds contribute to the blend's antioxidant capacity [39]. Additional analysis is necessary to understand the mechanisms by which ISP affects the composite's antioxidant properties and to determine the most effective ratios for maximizing these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of identification means we cannot attribute the antioxidant properties to these compounds specifically. The increase in radical scavenging capacity, despite a decrease in known antioxidant compounds like polyphenols, suggests that other non-polyphenolic compounds contribute to the blend's antioxidant capacity [39]. Additional analysis is necessary to understand the mechanisms by which ISP affects the composite's antioxidant properties and to determine the most effective ratios for maximizing these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…This includes reducing intestinal Th2-mediated immunity, altering TCR-mediated signaling cascades, and promoting Treg cell differentiation and function in lamina propria. The result is the preservation of immune tolerance, which is closely linked to the development of oral tolerance and the reduction in food allergies [ 238 , 239 , 240 , 241 ]. Specifically, research has shown that eating foods that are high in polyphenols, like cocoa flavonoids or apple-condensed tannins, can reduce the body’s sensitivity to an oral allergen and ward off food allergies.…”
Section: Possible Modes Of Action For Treating or Preventing Allergy-...mentioning
confidence: 99%